Fibro-adipogenic progenitor cells in skeletal muscle unloading: metabolic and functional impairments - Margarita Sorokina; Danila Bobkov; Natalia Khromova; Natalia Vilchinskaya; Boris Shenkman; Anna Kostareva; Renata Dmitrieva (Skeletal Muscle)
Abstract Background Skeletal muscle resident fibro-adipogenic progenitor cells (FAPs) control skeletal muscle regeneration providing a supportive role for muscle stem cells. Altered FAPs characteristics have been shown for a number of pathological conditions, but the influence of temporary functional unloading of healthy skeletal muscle on FAPs remains poorly studied. This work is aimed to investigate how skeletal muscle disuse affects the functionality and metabolism of FAPs. Methods Hindlimb suspension (HS) rat model employed to investigate muscle response to decreased usage. FAPs were purified from m. soleus functioning muscle (Contr) and after functional unloading for 7 and 14 days (HS7 and HS14). FAPs were expanded in vitro, and tested for: immunophenotype; in vitro expansion rate, and migration activity; ability to differentiate into adipocytes in vitro; metabolic changes. Crosstalk between FAPs and muscle stem cells was estimated by influence of medium conditioned by FAP’s on migration and myogenesis of C2C12 myoblasts. To reveal the molecular mechanisms behind unloading-induced alterations in FAP’s functionality transcriptome analysis was performed. Results FAPs isolated from Contr and HS muscles exhibited phenotype of MSC cells. FAPs in vitro expansion rate and migration were altered by functional unloading conditions. All samples of FAPs demonstrated the ability to adipogenic differentiation in vitro, however, HS FAPs formed fat droplets of smaller volume and transcriptome analysis showed fatty acids metabolism and PPAR signaling suppression. Skeletal muscle unloading resulted in metabolic reprogramming of FAPs: decreased spare respiratory capacity, decreased OCR/ECAR ratio detected in both HS7 and HS14 samples point to reduced oxygen consumption, decreased potential for substrate oxidation and a shift to glycolytic metabolism. Furthermore, C2C12 cultures treated with medium conditioned by FAPs showed diverse alterations: while the HS7 FAPs-derived paracrine factors supported the myoblasts fusion, the HS14-derived medium stimulated proliferation of C2C12 myoblasts; these observations were supported by increased expression of cytokines detected by transcriptome analysis. Conclusion the results obtained in this work show that the skeletal muscle functional unloading affects properties of FAPs in time-dependent manner: in atrophying skeletal muscle FAPs act as the sensors for the regulatory signals that may stimulate the metabolic and transcriptional reprogramming to preserve FAPs properties associated with maintenance of skeletal muscle homeostasis during unloading and in course of rehabilitation.